Education as a prominent state-building pillar: Orest Sikorskyi and the Balta Ukrainian Gymnasium (1917–1919) - Mishyn , Mykhailo (Skhid, 2025)
This article examines the role of Orest Sikorskyi (1880–1919), a Ukrainian educator, administrator, public and political figure, and organizer of the Ukrainian national movement in Balta and the Balta County of the Podillia Governorate, in the awakening of national consciousness among the local population amid revolutionary upheavals. Drawing on archival documents, eyewitness accounts, and contemporary scholarly research, the author considers O. Sikorskyi’s civic and educational activities in Balta as a significant local manifestation of the broader national struggle for Ukraine’s cultural and political self-determination. Born into a priestly family, O. Sikorskyi received a European education in History at the universities of Tartu and Halle, which shaped him as a representative of the modern intelligentsia: the profound moral and cultural values of his religious upbringing were integrated with a European worldview. His leadership of the commercial school in Balta, and later the Ukrainian gymnasium he founded, not only provided an institutional foundation for the development of national education but also fostered community cohesion in the face of prolonged political upheavals, war, and social instability. The tragic circumstances of his life underscore his dedication to Ukraine, and the lessons drawn from his experience remain relevant today, demonstrating the enduring connection between education and state-building.